SIKAP BAHASA SISWA KELAS XI SMA NEGERI 1 GEUMPANG TERHADAP BAHASA INDONESIA - Devy Wardani; Rajab Bahri; Razali Razali (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2020)
The aim of this study was to describe the language attitudes of XI grade students of State Senior High School 1 Geumpang towards the Indonesian language. The total number of students in grade XI students of the school for the 2019/2020 school year was 120 students. As many as 30 students were chosen as research respondents by using a random sampling technique. This research used a quantitative descriptive approach. The data were collected using questionnaires distributed to students. The data obtained from the questionnaires were analyzed by using the Likert Scale to measure attitude, with answer categories ranging from Strongly Agree (SA), Agree (A), Doubt (D), Disagree (DA), and Strongly Disagree (SD). All data obtained from the questionnaires were coded to facilitate the data analysis. The data processing was carried out in several stages, i.e. compiling the questions in the questionnaire, asking students to fill out a questionnaire, and analyzing the data. The data were classified into two groups, i.e. positive and negative attitudes. The results revealed that grade XI students of State Senior High School 1 of Geumpang showed a positive attitude towards the Indonesian language.